Kajian Etnozoologi Karya Agung Pengurip Gumi di Pura Luhur Batukaru, Tabanan, Bali - A. A. K. Suardana; N. W. N. A. Purwanti; I. W. Wahyudi (The Ethnobiological Society of Indonesia, 2021)
Indonesia has a diversity of biodiversity and a diversity of ethnic groups and languages which have been recorded more than 300 ethnic groups. One of the biodiversity in Indonesia is the variety of animal species that are scattered throughout Indonesia, with various uses from various ethnic groups. The relationship between humans in using animals is called ethnozoology. The purpose of this study is to determine the types and to determine the body parts of the animals used in Karya Agung Pengurip Gumi at Pura Batukau.This research is a descriptive study using a qualitative approach. The selection of respondents was carried out using the snowball sampling technique, namely by determining key respondents and then determining other respondents based on information from previous respondents. The key respondents in this study were the committee in Karya Agung Pengurip Gumi. The results showed that there were three classes of animals used as caru, including mammals, aves, and reptiles, and there were 11 species which were further divided into 19 different types based on differences in their physical characteristics. The parts of the body that are used are divided into six types, including the whole body parts, skin, head, blood, body fluids, and meat. Based on the research results, it is known that the number of species used as caru in Karya Agung Pengurip Gumi is 11, including: Bubalus bubalis, Capra sp., Bos javanicus, Chelonia mydas, Muntiacus muntjak, Cerpus timorensis, Paradoxurus hermaphrodites, Trachypithecus auratus, Cygnus sp., Canis familiaris, and Sus vittatus. Animal body parts that are used as caru in Pengurip Gumi's masterpiece include: whole body parts (55%), skin (15%), head (12%), blood (10%), meat (6%), and body fluids (2%).